Effects of moderate aerobic exercise, low-level laser therapy, or their combination on muscles pathology, oxidative stress and irisin levels in the mdx mouse model of Duchenne muscular dystrophy - ÖZBEYLİ, DİLEK (My University, 2022)
This study aimed to investigate how the combined use of low-level laser therapy (LLLT) and exercise, to reduce the possible side effects and/or increase the benefits of exercise, would affect oxidative stress, utrophin, irisin peptide, and skeletal, diaphragmatic, and cardiac muscle pathologies. In our study, 20 mdx mice were divided into four groups. Groups; sedentary and placebo LLLT (SC), sedentary and LLLT (SL), 30-min swimming exercise (Ex), and 30-min swimming exercise and LLLT (ExL). After 8 weeks of swimming exercise, muscle tests, biochemically; oxidative stress index (OSI), utrophin and irisin levels were measured. Skeletal, diaphragmatic and cardiac muscle histopathological scores, skeletal and cardiac muscle myocyte diameters were determined under the light and electron microscope. While only irisin levels were increased in group SL compared to SC, it was determined that OSI, heart muscle histopathological scores decreased and irisin levels increased in both exercise groups (p < 0.05). In addition, in the ExL group, an increase in rotarod and utrophin levels, and a decrease in muscle and diaphragm muscle histopathological scores were observed (p < 0.05). It was determined that the application of swimming exercise in the mdx mouse model increased the irisin level in the skeletal muscle, while reducing the OSI, degeneration in the heart muscle, inflammation and cardiopathy. When LLLT was applied in addition to exercise, muscle strength, skeletal muscle utrophin levels increased, and skeletal and diaphragmatic muscle degeneration and inflammation decreased. In addition, it was determined that only LLLT application increased the level of skeletal muscle irisin.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Biyomedikal Mühendisliği; Mühendislik ve Teknoloji; Medicine; Health Sciences; Surgery Medicine Sciences; Biomedical Engineering; Engineering and Technology; MÜHENDİSLİK, BİYOMEDİKAL; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); CERRAHİ; Klinik Tıp; Klinik Tıp (MED); ENGINEERING, BIOMEDICAL; ENGINEERING; Engineering, Computing & Technology (ENG); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); General Engineering; Engineering (miscellaneous); Bioengineering; Surgery; Physical Sciences; Duchenne; Mdx mice; Exercise; Low-level laser therapy; Irisin; Muscle; Heart; RAT SKELETAL-MUSCLE; DEGENERATION; CONTRACTILE; DYSFUNCTION; OXIDASE; MARKERS; MICE; FAT; Duchenne; Mdx mice; Exercise; Low-level laser therapy; Irisin; Muscle; Heart